Analisis Wacana Kritis Konten Viral Kang Dedi di Instagram sebagai Media Disiplin Anak - Mohamad Edwan Faturohman; Yandi Hermawandi; Resty Mustika Pratiwi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the viral video phenomenon of Kang Dedi delivering disciplinary messages to children through social media, particularly Instagram Reels, within the socio-cultural context of West Java society. The analysis employs Norman Fairclough’s critical discourse analysis framework, focusing on the textual, discursive practice, and socio-cultural practice dimensions. Findings reveal that the video functions not only as an effective mass communication tool but also reflects shifts in authority patterns and parenting in the digital era. The massive dissemination supported by social media algorithms expands the message’s reach, influencing children’s behavior and parental approaches. Furthermore, the cultural background and natural environment of West Java strengthen the public figure’s image as a close and caring leader. This research offers valuable insights for developing educational communication strategies that integrate technology with local cultural values. Future studies are recommended to conduct cross-cultural comparisons and explore the psychological impact of social media-based and disciplinary methods.